2021
DOI: 10.1039/d0fo03261a
|View full text |Cite
|
Sign up to set email alerts
|

Mucuna pruriens treatment shows anti-obesity and intestinal health effects in obese rats

Abstract: This study evaluated anti-obesity effect and intestinal health of obese rats treated with MP, focusing on food consumption and somatic, biochemical, and histological parameters. 32 Wistar rats with ± 40...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…This result therefore suggests that Mn and M. pruriens leaves could play a role in decreasing body However, the data also suggest that M. pruriens impact on body weight reduction could be dose dependent as 20% constituted M. pruriens feed showed a more drastic decrease in body weight compared to control rats. This finding is supported by previous studies (Salaam et al 2019;Tavares et al 2021), who reported decreased body weight and physical activities of rats treated with ethanol extract of M. pruriens leaves, and attributed same to the metabolic changes produced by the chemical constituents.…”
Section: Discussionsupporting
confidence: 89%
“…This result therefore suggests that Mn and M. pruriens leaves could play a role in decreasing body However, the data also suggest that M. pruriens impact on body weight reduction could be dose dependent as 20% constituted M. pruriens feed showed a more drastic decrease in body weight compared to control rats. This finding is supported by previous studies (Salaam et al 2019;Tavares et al 2021), who reported decreased body weight and physical activities of rats treated with ethanol extract of M. pruriens leaves, and attributed same to the metabolic changes produced by the chemical constituents.…”
Section: Discussionsupporting
confidence: 89%
“…Animal faeces were collected on the 26 th to 28 th days of the experiment to obtain samples in representative quantities for analysis (Batista et al 2018, Tavares et al 2021. Part of the faecal samples was collected fresh for bacterial count analysis and part was stored in a freezer -20°C for pH and moisture analysis.…”
Section: Faecal Analysesmentioning
confidence: 99%
“…The cafeteria diet consisted of commercial feed (Presence®, Paulínia, Brazil) and processed foods such as cookies, corn chips, sausages, cakes, and chips, among other foods considered hypercaloric. 11,29,33 The processed foods were distributed on a menu, in which four foods were offered and commercial feed on each day of the week (Table S2 †). The respective foods were administered separately, served in 5 cm pieces inside glass jars with quantity ad libitum.…”
Section: Study Design Coconut Oil Administration Protocol and Monitor...mentioning
confidence: 99%
“…The healthy groups received a commercial feed or control diet (Presence®, Paulínia, Brazil) with 3.1 kcal g −1 , 57 kcal % carbohydrates, 28 kcal % protein, 14 kcal % lipids (Table S3 †). 29,33 Food consumption and food preference (in grams) for the OG and OGCO groups were evaluated daily and calculated from the amount offered of processed foods and commercial feed minus leftovers (waste), respectively. Each day, the obesity-induced rats had the option of consuming the commercial chow (Presence®, Paulínia, Brazil) and/or four different foods, which made it possible to analyse the food preference of the OG and OGCO rats over the 16 weeks of the study.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation